Stereoretentive Palladium‐Catalyzed Arylation, Alkenylation, and Alkynylation of 1‐Thiosugars and Thiols Using Aminobiphenyl Palladacycle Precatalyst at Room Temperature. Issue 23 (15th April 2015) - Bruneau, Alexandre; Roche, Maxime; Hamze, Abdallah; Brion, Jean‐Daniel; Alami, Mouad; Messaoudi, Samir
Abstract A general and efficient protocol for the palladium‐catalyzed functionalization of mono‐ and polyglycosyl thiols by using the palladacycle precatalyst G3‐XantPhos was developed. The CS bond‐forming reaction was achieved rapidly at room temperature with various functionalized (hetero)aryl‐, alkenyl‐, and alkynyl halides. The functional group tolerance on the electrophilic partner is typically high and anomer selectivities of thioglycosides are high in all cases studied. New sulfur nucleophiles such as thiophenols, alkythiols, and thioaminoacids (cysteine) were also successfully coupled to lead to the most general and practical method yet reported for the functionalization of thiols.